2017
DOI: 10.1130/g38931.1
|View full text |Cite
|
Sign up to set email alerts
|

The rise and fall of stromatolites in shallow marine environments

Abstract: Stromatolites are abundant in shallow marine sediments deposited before the evolution of animals, but in the modern ocean they are restricted to locations where the activity of animals is limited. Overall decline in the abundance of stromatolites has, therefore, been attributed to the evolution of substrate-modifying metazoans, with Phanerozoic stromatolite resurgences attributed to the aftermaths of mass extinctions. Here we use a comprehensive stratigraphic database, the published literature, and a machine r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(51 citation statements)
references
References 35 publications
2
47
0
2
Order By: Relevance
“…These types of known relationships can be leveraged during machine reading and learning tasks to help identify entities and improve the quality of machine-driven geological data extraction and inference tasks 30,31 . Here, we describe the motivation for Macrostrat and its general data model.…”
Section: Alexander Ronovmentioning
confidence: 99%
“…These types of known relationships can be leveraged during machine reading and learning tasks to help identify entities and improve the quality of machine-driven geological data extraction and inference tasks 30,31 . Here, we describe the motivation for Macrostrat and its general data model.…”
Section: Alexander Ronovmentioning
confidence: 99%
“…Another solution is to further streamline data input systems that prepare data and metadata in import-ready formats for Neotoma, at the earliest stages of scientific workflows (e.g., building customized import software for data generated from mass spectrometers or for microfossil analysts working at microscopes). A third is to make use of text-mining programs such as GeoDeepDive (Peters et al, 2014(Peters et al, , 2017 for help to discover and bring online dark data (Heidorn, 2008) and automating the discovery of new papers and the particularly routine parts of data entry, such as bibliographic citations. We welcome innovation by others in all of these areas.…”
Section: Adding Data To Neotomamentioning
confidence: 99%
“…Elevated snail mortality implies periods of reduced predation on microbial films, the food source of the aquatic snails 47 . The coexistence of macroinvertebrates and marine stromatolites has recently been reported for a site in South Africa 16 , suggesting that metazoan co-occurrence may play a reduced role in limiting stromatolite growth 48 , 49 . However, we observed that areas with abundant living snails, including Phrantela , the largest of the gastropod species that could potentially cause significant damage by grazing, did not coincide with patches of stromatolite occurrence.…”
Section: Resultsmentioning
confidence: 98%